Host-country characteristics, international intra-firm technology transfer and organizational sustainability performance-multinational corporations in Malaysia - Syed Ali Fazal (2019)
This study examined the effect of host-country characteristics (i.e. market environment, cultural distance, government policies, and absorptive capacity) on international intra-firm technology transfer and organizational sustainability performance among subsidiaries of foreign-based multinational corporations (MNCs) in Malaysia, under the premises of stakeholder theory and resource-based view. Quantitative data was collected from randomly selected 252 foreign-based MNCs in Malaysia. Findings of this study revealed that market environment, cultural distance and absorptive capacity have a positive and significant effect on international intra-firm technology transfer; and the positively significant impact of international intra-firm technology transfer on organizational sustainability performance. Findings of this study further revealed significant mediating effect of international intra-firm technology transfer on the relationships between host-country characteristics and sustainability performance of the MNC subsidiaries. It is recommended that Governments of emerging economies such as Malaysia, formulate policies for a more competitive market environment and support their citizens to acquire relevant education, skills, and cultural awareness that would enhance technological inflows accompanying foreign direct investments leading towards superior economical, social and environmental performance in organizations